(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
The metal processing industry has historically had a large role and importance for the Croatian economy. The current picture of the economy reflects the historical situation, trends and events that are described in the paper. In order to understand macroeconomic indicators and certain events, it is important to analyse the macro-environment, because it greatly affects the development and operations of an enterprise. The general economic climate is explained, as well as its underlying indicators that affect the competitiveness. The goal of this paper is to show lessons learned regarding the impact of the metal processing industry on industrial production in Croatia during the period of recession. These lessons might indicate how to find the best business strategy that will enable the development and prosperity of enterprises in the global market in the future. There are no rules or definitions for achieving success. The enterprise must define its pathway if it wants to accomplish its goals - because an enterprise without strategy is like a ship without a rudder. There is a growing emphasis on the importance of industrial production, so the metal processing industry today shows signs of a slight recovery and growth, which still cannot be compared with the previous situation.